Expanded genetic insight and clinical experience of DNMT1-complex disorder. (August 2020) - Bi, Hongyan; Hojo, Kaori; Watanabe, Masashi; Yee, Christina; Maski, Kiran; Saba, Sadaf; Graff-Radford, Jonathan; Machulda, Mary M.; St Louis, Erik K.; Humes, Ilona Spitsyna; Flanagan, Eoin P.; Nicolau, Stefan; et al.
Abstract : Objective: To report novel causal mutations, expanded clinical phenotypes, and clinical management of DNA methyltransferase 1 (DNMT1)-complex disorder. Methods: Neurophysiologic testing, imaging, and genetic findings were summarized in clinical context for 5 cases with DNMT1-complex disorder. Results: We identified 2 novel DNMT1 mutations (p.E510K and p.P1546A) by whole-exome sequencing (WES). Case 1 (p.E510K) presented with childhood ataxia, treatment-refractory seizures, and rapid cognitive decline in his 50s. Case 2 also had childhood onset and presented with seizures, language regression, hearing loss, narcolepsy with cataplexy symptoms, optic atrophy, sensory neuropathy, and hypogammaglobulinemia requiring IV immunoglobulin. Case 2 (p.P1546A) was identified with a de novo and the first mutation residing outside the targeting sequence domain. Case 3 (p.A570V) had paralytic asymmetric onset attacks triggered by emotionality and lasting sometimes for weeks. Neuropsychological testing showed executive dysfunction localizing to frontosubcortical and frontoparietal structures. He gradually developed left predominant brain atrophy. MRI showed T2 hyperintense lesions that enhanced on T1 postgadolinium images, and brain PET showed hypometabolism in atrophied regions. Case 4 (p.T497P) underwent left cochlear implant, resulting in significant hearing improvements at all tested frequencies (250–6, 000 Hz). Case 5 (p.Y511H) had profound gait ataxia with posterior column atrophy of the spinal cord and abnormal evoked potentials primarily affecting the fasciculus gracilis. Conclusions: Broader application of WES further expands genotype-phenotype correlations of DNMT1-complex disorder. Two mutations are identified with early childhood onsets. The expanded new phenotypes include asymmetric brain hemiatrophy with parenchymal gadolinium enhancement, spinal cord atrophy, prolonged cataplectic spells, and hypogammaglobulinemia. Hearing loss treatment by cochlear implantation is helpful and should be considered.